2017
DOI: 10.18632/oncotarget.v8i8
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: News on: The repurposed anthelmintic mebendazole in combination with trametinib suppresses refractory NRASQ61K melanoma by Dean Rosenthal, et al. Oncotarget, 2016, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The composition of the tumor-infiltrating T cell compartment correlates with patient survival. [43][44][45][46] Our study now showed that a correlation also exists between this composition and the likelihood that cytokine-producing tumor-reactive T cells are present in expanded TIL products. In line with previous studies that showed that the presence of CD8 + T cells expressing CD103 and CD69 serves as a favorable prognostic marker for survival, 43,44,47 we describe here that their presence in the tumor lesion also correlated with high percentages of cytokine-producing CD8 + T cells in the TIL products.…”
Section: Discussionsupporting
confidence: 51%
“…The composition of the tumor-infiltrating T cell compartment correlates with patient survival. [43][44][45][46] Our study now showed that a correlation also exists between this composition and the likelihood that cytokine-producing tumor-reactive T cells are present in expanded TIL products. In line with previous studies that showed that the presence of CD8 + T cells expressing CD103 and CD69 serves as a favorable prognostic marker for survival, 43,44,47 we describe here that their presence in the tumor lesion also correlated with high percentages of cytokine-producing CD8 + T cells in the TIL products.…”
Section: Discussionsupporting
confidence: 51%
“…In the study by Marc R, results showed that the level of YKT6 can influence the prognostic outcomes of NSCLC patients following surgery, higher levels were predicted to have shorter disease-free survival and overall survival ( 56 ). Biomarkers in exosomes that have prognostic value in lung cancer include let-7a-5p, miR-21, miR- 106b, miR-486-5p, miR-23b-3p, miR-10b-5p, and miR-21-5p ( 62 66 ).…”
Section: Discussionmentioning
confidence: 99%